Market Orientation And Product Innovation In Improving Competitive Advantage And Its Impact On Market Performance - Suharti, Suharti; Nurhasanah, Nurhasanah; Anissa, Zalsa; Yusuf, Yusuf (International Journal of Social Service and Research, 2024)
Small and Medium Enterprises are one of the important parts that support the economy in Indonesia. This research was conducted to analyze market influencers. and PR innovations in increasing competitive advantage and its impact on market performance. The object of this research is Small and Medium Enterprises entrepreneurs in Cirebon Regency, Java, Barat, especially Small and Medium Enterprises that are still operating to this day. The population in this study is MSME owners or managers. Sampling in this study used responsve sampling of 100 people. Using a quantitative method with data analysis using SPSS 21. The results of this study show that the market orients Having a significant impact on competitive advantage in the performance of marketers and then from the results of PR innovation research also has a positive impact on competitive advantage in the performance of marketers and the results of the latest research. namely the advantage of direct competition in the market.